CURATING ACCESS : disability art activism and creative accommodation - Cachia, Amanda, 1978- ([S.l.] : ROUTLEDGE, 2022)
This book is an interdisciplinary collection of twenty-four essays which critically examine contemporary exhibitions and artistic practices that focus on conceptual and creative aspects of access. Oftentimes exhibitions tack on access once the artwork has already been executed and ready to be installed in the museum or gallery. But what if the artists were to ponder access as an integral and critical part of their artwork? Can access be creative and experimental? And furthermore, can the curator also fold access into their practice, while working collaboratively with artists, considering it as a theoretical and practical generative force that seeks to make an exhibition more engaging for a wider diversity of audiences? This volume includes essays by a growing number of artists, curators, and scholars who ponder these ideas of ad-hoc, experimental and underground approaches within exhibition-making and artistic practices. It considers how, through these nascent exhibition models and art practices, enhanced experiences of access in the museum can be a shared responsibility amongst museum workers, curators, and artists, in tandem with the public, so that access becomes a zone of intellectual and creative "accommodation," rather than strictly a discourse on policy. The book provides innovative case studies which provide a template for how access might be implemented by individuals, artists, curators, museum administrators and educators given the growing need to offer as many modalities of access as possible within cultural institutions. This book shows that anyone can be a curator of access and demonstrates how to approach access in a way that goes beyond protocol and policy. It will thus be of interest to students and scholars engaged in the study of museums, art history and visual culture, disability, culture, and communication.
OCLC-licensed vendor bibliographic record.
Keywords: Museums and people with disabilities; Museums -- Barrier-free design; ART / Collections, Catalogs, Exhibitions; SOCIAL SCIENCE / Handicapped